2007
DOI: 10.1093/europace/eum262
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical dyssynchrony by 3D echo correlates with acute haemodynamic response to biventricular pacing in heart failure patients

Abstract: The present study suggests that mechanical dyssynchrony measured by RT3DE shows a good correlation with invasively determined acute haemodynamic response to biventricular pacing in patients with symptomatic dilated cardiomyopathy. Future studies are needed to further define the clinical utility of RT3DE in identifying patients who are most likely to respond to cardiac resynchronization therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
1
27
1
2
Order By: Relevance
“…18,19 Despite restricting analysis to patients with optimal images, we did not observe high predictive accuracy with this methodology. Limitations in temporal resolution with 3D echocardiography and poor reproducibility may have hindered accurate detection of dyssynchonous contraction and contributed to our findings.…”
Section: Is One Dyssynchrony Index Better Than Others?contrasting
confidence: 63%
“…18,19 Despite restricting analysis to patients with optimal images, we did not observe high predictive accuracy with this methodology. Limitations in temporal resolution with 3D echocardiography and poor reproducibility may have hindered accurate detection of dyssynchonous contraction and contributed to our findings.…”
Section: Is One Dyssynchrony Index Better Than Others?contrasting
confidence: 63%
“…It also has been suggested that longitudinal dyssynchrony may be subject to higher variability and may correlate less well with ventricular functional recovery after CRT than 2-dimensional strain techniques that evaluate radial dyssynchrony. 20 Other potentially interesting methods for further study are novel echocardiographic techniques, including 2-dimensional strain imaging (speckle tracking approach), 21 3-dimensional echocardiography, 22 anatomic M-mode imaging, 23 and magnetic resonance imaging. 24 Were the cutoff points for the echocardiographic measurements appropriately selected?…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional echocardiography is another potential modality for quantification of dyssynchrony and prediction of the effect of CRT. 40,41 Several different mechanisms may be involved in CRT, and the best patient selection method may require several combined and/or stepwise approaches other than the single intraventricular dyssynchrony index.…”
Section: Prediction Of the Effect Of Crt By Assessment Of Strain-derimentioning
confidence: 99%